Psychosocial and organizational determinants of safe food handling at retail and food service establishments: a systematic review and meta-analysis. Issue 4 (4th July 2019) - Young, Ian; Thaivalappil, Abhinand; Waddell, Lisa; Meldrum, Richard; Greig, Judy
ABSTRACT: Various psychosocial and organizational factors have been investigated as determinants of food handlers' food safety behaviours. A systematic review and meta-analysis of studies in this area was conducted to identify and synthesize the key behavioural determinants. Standard systematic review steps were followed: comprehensive search strategy; relevance screening; article characterization; risk of bias assessment; data extraction; and random-effects meta-analysis. Sixty-two relevant studies were identified, and knowledge was the most commonly investigated behavioural determinant ( n = 51). Increased knowledge was consistently associated with safe food handing behaviours across both correlation ( r = 0.30; 95% confidence interval [CI]: 0.12, 0.46; n = 24 studies; I 2 = 98%) and odds ratio (OR) measures (adjusted OR = 1.85; 95% CI: 1.27, 2.70; n = 3; I 2 = 0%). Seven other behavioural determinant categories were also consistently associated with various food safety behaviour outcomes. In contrast, no association was found between food handler experience and behaviour. The findings can inform the development of targeted training initiatives for food handlers.